The Academic Impact of Student Employment: A Pilot Study. - Peak, Katherine R. (Radiologic Science & Education, 2019)
The majority of today's college students are employed, resulting in dual roles as full-time student and part-time or even full-time employee. This situation seems as if it would limit the amount of time students have for studying and completing assignments, thereby having a negative impact on their academic performance. This study used a survey and grade point averages (GPAs) to examine the work and study habits of 44 students in an imaging sciences program to determine the effects of working on academic achievement. The results of a linear regression analysis suggested there is no statistically significant difference in the GPAs of working students compared with unemployed students, and that employed students are able to strike a balance between their work and study habits. Employment seemed to cause no significant negative effect to the academic performance of students compared with their non-working counterparts.